Repertório barroco e suas possibilidades ao violão: aspectos teóricos e métodos transcritivos a partir das cordas dedilhadas - Cardoso, Renato de Carvalho [UNESP] (2014)
This study proposes a dialogue across fields of Early Music and the Interpretative Practices in modern instruments. For this, it discusses the ideological basis of the Historically Informed PerformanceMovement which tends to create a distance between such areas, especially the paradigmatic association between early music and period instruments. Aiming to develop a method of arrangement of the repertoire of baroque guitar, theorbo and baroque lute for the modern guitar, this study has departed from the literature review of editions and academic literature about guitar arrangement of the baroque repertoire, with emphasis on the aforementioned instruments. These publications have been classified according to their method of transcription, thus categorizing them from the alteration of the tuning of the guitar. I propose the direct arrangement method to the repertoire of plucked string instruments of the Baroque, which consists of changing the guitar tuning according to the reference instrument's repertoire, allowing a direct reading of the tablature, with delimited tools for adaptation of the musical text, without the need of editing the music. Thisproposal allows for a perennial contact with the primary sources and its notation forms, in addition to providing an ease of execution and a large amount of arrangement.